Battery preparation method and battery

The tube SOEC single cell was prepared by the mold method, and the microstructure and thickness of the electrode and electrolyte layer were optimized, which solved the complex problems of sealing and preparation of flat plate SOECs, and achieved efficient and stable battery performance and long-term working ability.

CN119833647APending Publication Date: 2025-04-15PETROCHINA SHENZHEN NEW ENERGY RESEARCH INSTITUTE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311321840.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-12
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing flat-panel solid oxide electrolytic batteries (SOECs) have problems such as difficulty in sealing, uneven heat distribution, uneven temperature distribution, resulting in battery cracks, poor mechanical properties, and easy to cause air leakage, power density drop, and even combustion or explosion. The preparation of tube SOECs is complex and costly.

Method used

Tube SOEC single cells are prepared by mold method. By uniformly coating the electrode and electrolyte slurry on the mold rod, layer by layer, forming anode, electrolyte and cathode film layers, optimizing the microstructure and controlling the thickness, achieving rapid and low-cost mass production of high repeatability and high-performance batteries.

Benefits of technology

Reducing ion conduction impedance, improving electrochemical performance and long-term working stability, solving problems such as sealing difficulties and complex preparation, and achieving efficient and stable battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833647A_ABST
    Figure CN119833647A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid oxide electrolytic cells, and provides a battery preparation method and a battery, and the battery preparation method comprises the following steps: uniformly coating a mold rod with electrode slurry, forming an anode film layer on the mold rod, and carrying out first-stage sintering treatment on the anode film layer to obtain a hydrogen electrode; uniformly covering a hydrogen electrode with the electrolyte slurry, forming an electrolyte layer on the hydrogen electrode, and performing second-stage sintering treatment on the electrolyte layer to obtain an electrolyte membrane layer; and uniformly coating the electrode slurry on the electrolyte membrane layer, forming a cathode membrane layer on the electrolyte membrane layer, and carrying out third-stage sintering treatment on the cathode membrane layer to obtain the oxygen electrode. Wherein the anode film layer, the electrolyte layer and the cathode film layer are laminated, the anode film layer and the cathode film layer are separated by the electrolyte layer, and the two ends of the oxygen electrode are cut and sealed to obtain the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solid oxide fuel cells, and in particular to a battery preparation method and a battery. Background Art

[0002] At present, the flat-plate solid oxide electrolysis cell (SOEC) stack is difficult to seal, the heat distribution is uneven, the heat control is difficult, and the uneven temperature distribution causes cracks in the battery. In addition, the 2D structure of the flat-plate battery has poor mechanical properties, and large temperature fluctuations can easily cause the battery to rupture, leading to gas leakage, power density and open circuit voltage drops, and even cause combustion or explosion. Tubular fuel cells are easy to seal, have uniform heat exchange, and have better mechanical properties of 3D structures, but the preparation process and technology are complex. Summary of the invention

[0003] In view of this, the present application provides a battery preparation method and a battery.

[0004] Specifically, the present application is implemented through the following technical solutions:

[0005] According to the first aspect of the present application, a battery preparation method is provided, the battery preparation method comprising: uniformly coating an electrode slurry on a mold rod, forming an anode film layer on the mold rod, and performing a first-stage sintering treatment on the anode film layer to obtain a hydrogen electrode; uniformly covering an electrolyte slurry on the hydrogen electrode, forming an electrolyte layer on the hydrogen electrode, and performing a second-stage sintering treatment on the electrolyte layer to obtain an electrolyte membrane layer; uniformly coating an electrode slurry on the electrolyte membrane layer, forming a cathode film layer on the electrolyte membrane layer, and performing a third-stage sintering treatment on the cathode film layer to obtain an oxygen electrode, wherein the anode film layer, the electrolyte layer and the cathode film layer are stacked, and the anode film layer and the cathode film layer are separated by the electrolyte layer; and cutting and sealing the two ends of the oxygen electrode to obtain a battery.

[0006] The battery preparation method in the technical solution of the present application is specifically a process method for preparing a tubular SOEC single battery by a mold method, wherein an electrode slurry is prepared by mixing and grinding an electrode material and an electrode auxiliary material, and an electrolyte slurry is prepared by mixing and grinding an electrolyte and an electrolyte auxiliary material. The electrode slurry is evenly coated on the mold rod, i.e., the graphite rod, to form an anode film layer on the graphite rod, and the anode film layer is subjected to a first-stage sintering treatment to obtain an anode ceramic film layer, i.e., a hydrogen electrode; the electrolyte slurry is evenly coated on the electrode of the anode film layer, i.e., the electrolyte slurry is coated on the anode ceramic film layer of the hydrogen electrode, and an electrolyte layer is formed on the anode ceramic film layer of the hydrogen electrode, and the electrolyte layer is subjected to a second-stage sintering treatment to obtain an electrolyte film layer, i.e., an electrolyte ceramic film layer; the electrode slurry is then evenly coated on the electrolyte film layer, to form a cathode film layer on the electrolyte film layer, and the cathode film layer is subjected to a third-stage sintering treatment to obtain a cathode ceramic film layer, i.e., an oxygen electrode, i.e., a blank SOEC single cell, consisting of the anode ceramic film layer, the electrolyte ceramic film layer, and the cathode ceramic film layer is stacked; both ends of the oxygen electrode, i.e., a blank SOEC single cell, which is composed of the anode ceramic film layer, the electrolyte ceramic film layer, and the cathode ceramic film layer, are cut to obtain a single cell that can be sealed and tested. In this preparation process, the anode supporting the battery is porous, with a thickness of 50 to 500 μm as required. The thickness of the electrolyte layer is controlled to 5 to 10 μm through precision casting to reduce the ion conductivity impedance; the thickness of the oxygen electrode with low ion and electronic conductivity is reduced to optimize its microstructure. The electrochemical performance and long-term working stability of the battery are improved by optimizing the microstructure of each layer and controlling the thickness. The shortcomings of the previous use of flat SOECs, such as the difficulty in sealing, are changed, and the shortcomings of the complex preparation and low efficiency of tubular SOECs are solved. SOEC single cells with high repeatability and high performance can be prepared quickly, at low cost, and in large quantities.

[0007] According to the second aspect of the present application, a battery is provided, specifically a tubular SOEC battery, which is prepared by the battery preparation method in any possible implementation of the first aspect, that is, it is prepared by the process method for preparing a tubular SOEC single battery by the mold method in any possible implementation of the first aspect.

[0008] The technical solution provided by this application brings at least the following beneficial effects:

[0009] Reduce the thickness of the electrolyte layer and the ion conduction impedance; reduce the thickness of the oxygen electrode with low ion and electronic conductivity and optimize its microstructure. By optimizing the microstructure of each layer and controlling the thickness, the electrochemical performance and long-term working stability of the battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0011] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or related technical descriptions are briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0012] Figure 1 One of the flow diagrams of a battery preparation method provided in an embodiment of the present application;

[0013] Figure 2 A second schematic flow chart of a battery preparation method provided in an embodiment of the present application;

[0014] Figure 3 A third flow chart of a battery preparation method provided in an embodiment of the present application;

[0015] Figure 4 A fourth flow chart of a battery preparation method provided in an embodiment of the present application;

[0016] Figure 5 A fifth flow chart of a battery preparation method provided in an embodiment of the present application;

[0017] Figure 6 A sixth flow chart of a battery preparation method provided in an embodiment of the present application;

[0018] Figure 7 A seventh flow chart of a battery preparation method provided in an embodiment of the present application;

[0019] Figure 8 The eighth flow chart of a battery preparation method provided in an embodiment of the present application;

[0020] Fig. 9 A ninth flow chart of a battery preparation method provided in an embodiment of the present application;

[0021] Fig.10 A tenth flow chart of a battery preparation method provided in an embodiment of the present application;

[0022] Fig.11 11 is a flow chart of a battery preparation method provided in an embodiment of the present application;

[0023] Fig.12 A schematic diagram of the preparation process of a battery provided in an embodiment of the present application. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0025] See also Figure 1 , the present application embodiment provides a battery preparation method, the method may include the following steps:

[0026] S102, uniformly coating the electrode slurry on the mold rod to form an anode film layer on the mold rod, and performing a first-stage sintering treatment on the anode film layer to obtain a hydrogen electrode;

[0027] S104, uniformly covering the hydrogen electrode with electrolyte slurry to form an electrolyte layer on the hydrogen electrode, and performing a second-stage sintering treatment on the electrolyte layer to obtain an electrolyte membrane layer;

[0028] S106, uniformly coating the electrode slurry on the electrolyte membrane layer, forming a cathode membrane layer on the electrolyte membrane layer, and performing a third-stage sintering treatment on the cathode membrane layer to obtain an oxygen electrode;

[0029] S108, cutting and sealing the two ends of the oxygen electrode to obtain a battery.

[0030] In this embodiment, a battery preparation method is provided, which is used to prepare a battery. Specifically, the present invention prepares an electrode slurry by mixing and grinding an electrode material and an electrode auxiliary material, and prepares an electrolyte slurry by mixing and grinding an electrolyte and an electrolyte auxiliary material. A casting process is performed on a mold rod, i.e., a graphite rod, by hand or by a casting machine. Specifically, the electrode slurry NiO-SDC (or Cu 0.15 Ni 0.85 O-SDC、Co 0.2 Ni 0.8 O-SDC, NiO-YSZ, Cu 0.2 Ni 0.8 O-YSZ、Co 0.2 Ni 0.8 O-YSZ、Cu 0.15 Ni 0.85 O-BZSYYb, CoNiO-BZSYYb, NiO-BZSYYb, etc.) are coated on the mold rod to form an even electrode film layer, i.e., an electrode rod with an anode film layer. The amount of electrode film used is 0.5g / cm 2 ~1g / cm 2Specifically, the amount of electrode slurry can be adjusted according to the required thickness, and pore-forming graphite, pore-forming fiber, etc. can be added according to the pore-forming requirements. After the electrode is coated, the temperature is controlled to 700°C and sintered for 2 hours under a nitrogen atmosphere to form a 10 cm long supported porous electrode to obtain an anode ceramic membrane layer, namely a hydrogen electrode.

[0031] Further, the anode film electrode is processed by hand or by a tape casting machine, and the electrolyte YSZ (or SDC, LSGM, BZSYYb and other ceramic materials) slurry is coated on the electrode rod to form a uniform electrode film layer, i.e., the electrolyte layer. The amount of the electrolyte layer is 0.2 g / cm 2 ~0.5g / cm 2 The specific thickness can be adjusted according to the required thickness, and then the temperature is controlled to be 1350°C for sintering for 4 hours in an air atmosphere to form a dense electrolyte ceramic layer, namely the electrolyte membrane layer, which completely covers and wraps the supporting electrode layer. The length of the electrolyte ceramic layer is 11 cm, and its length can be adjusted as needed.

[0032] Further, an oxygen evolution electrode layer, i.e., a cathode, is coated, and the cathode material is NiO-SDC (or LSM-SDC, LSCF-SDC, NiO-YSZ, Cu 0.15 Ni 0.85 O-YSZ、Co 0.2 Ni 0.8 O-YSZ, LSM-BZSYYb, LSCF-BZSYYb, NiO-BZSYYb, etc.), specifically, the electrode slurry is evenly coated on the electrode of the electrolyte membrane layer, a cathode film layer is formed on the electrode of the electrolyte membrane layer, and the cathode film layer is subjected to a third-stage sintering treatment to obtain a cathode ceramic film layer. The amount of the electrode film is 0.5 g / cm 2 ~1g / cm 2 Specifically, the amount of electrode slurry can be adjusted according to the required thickness, and pore-forming graphite, pore-forming fiber, etc. can be added according to the pore-forming requirements. After the electrode is coated, the temperature is controlled to be 800°C for sintering for 4 hours in an air atmosphere to form a 9cm long oxygen-evolving ceramic electrode, i.e., a cathode ceramic membrane layer. Among them, the anode ceramic membrane layer, the electrolyte ceramic membrane layer, and the cathode ceramic membrane layer are stacked, and the electrolyte membrane layer completely separates the anode ceramic membrane layer from the cathode ceramic membrane layer.

[0033] Furthermore, the blank SOEC battery consisting of the anode ceramic membrane layer, the electrolyte ceramic membrane layer and the cathode ceramic membrane layer is cut by laser cutting, and the length of the battery after cutting is 9.5cm to 10cm, so as to obtain a battery with a flat end cut. It can be understood that a graphite rod with a surface layer having micron pores, 18cm long, 2cm in diameter, and 99.99% purity is used as a mold, and the electrodes and electrolytes are cast or sprayed layer by layer, and dried and sintered layer by layer.

[0034] This application utilizes a mold method combined with a slurry configuration process to rapidly prepare a tubular (SOEC) single cell with good repeatability at low cost. The electrochemical performance of the battery is improved by optimizing the electrode microtube structure and controlling the process of thinning the electrolyte thickness. The problem of sealing the flat-plate SOEC high-temperature stack is solved. The flat-plate stack has a high power density per unit volume, but because the space between the batteries is small, it leads to uneven gas circulation and exchange, uneven heat exchange, and poor long-term operating stability caused by poor sealing, and short battery and stack life. And solve the problems of high cost, long cycle, and complex preparation process of previous tubular SOEC preparation.

[0035] Among them, in the present application, the anode film layer, i.e., the anode ceramic film layer, is the hydrogen electrode of SOEC, the electrolyte film layer, i.e., the electrolyte ceramic film layer, is the SOEC electrolyte, and the cathode film layer, i.e., the cathode ceramic film layer, is the oxygen electrode of SOEC.

[0036] In some embodiments, the coating amount of the anode film layer is 0.5 g / cm 2 ~1g / cm 2 , the length of the anode film layer is 9cm to 11cm.

[0037] Specifically, the coating amount of the anode film layer can be 0.5 g / cm 2 , the coating amount of the anode film can be 1g / cm 2 The coating amount of the anode film can also be 0.8g / cm 2 The length of the anode film layer is adjustable from 1 to 20 cm according to the preparation requirements.

[0038] Based on the same inventive concept, see Figure 2 , the present application embodiment provides a battery preparation method, the method may include the following steps:

[0039] S202, uniformly coating the electrode slurry on the mold rod to form an anode film layer on the mold rod, placing the mold rod coated with the anode film layer in a nitrogen environment, and sintering the mold rod at a first preset temperature for a first time to obtain a hydrogen electrode;

[0040] S204, uniformly covering the hydrogen electrode with electrolyte slurry to form an electrolyte layer on the hydrogen electrode, and performing a second-stage sintering treatment on the electrolyte layer to obtain an electrolyte membrane layer;

[0041] S206, uniformly coating the electrode slurry on the electrolyte membrane layer, forming a cathode membrane layer on the electrolyte membrane layer, and performing a third-stage sintering treatment on the cathode membrane layer to obtain an oxygen electrode;

[0042] S208, cutting and sealing the two ends of the oxygen electrode to obtain a battery.

[0043] In this embodiment, the electrode rod coated with the anode film layer is placed in a nitrogen environment and sintered at a first preset temperature for a first time, wherein the first preset temperature is 600° C. to 800° C. and the first time is 1 hour to 3 hours.

[0044] Specifically, the electrode slurry is evenly coated on the electrode rod to form an anode film layer on the electrode rod, the electrode rod coated with the anode film layer is placed in a nitrogen environment, and sintered at a first preset temperature for a first time to obtain an anode ceramic film layer, i.e., a hydrogen electrode;

[0045] Further, the electrolyte slurry is evenly coated on the anode ceramic membrane layer to form an electrolyte layer on the anode ceramic membrane layer electrode, and the electrolyte layer is subjected to a second stage sintering treatment to obtain an electrolyte ceramic membrane layer, i.e., an electrolyte membrane layer;

[0046] Further, the electrode slurry is evenly coated on the electrolyte ceramic film layer, a cathode film layer is formed on the electrolyte ceramic film layer, and the cathode film layer is subjected to a third-stage sintering treatment to obtain a cathode ceramic film layer, i.e., an oxygen electrode;

[0047] Furthermore, the SOEC blank battery consisting of the anode ceramic membrane layer, the electrolyte ceramic membrane layer and the cathode ceramic membrane layer is cut to obtain a battery that can be sealed and tested.

[0048] In some embodiments, the first preset temperature is 600° C. to 800° C., and the first time period is 1 hour to 3 hours.

[0049] Specifically, the first preset temperature may be 600° C., the first preset temperature may be 700° C., the first preset temperature may also be 800° C., the first time length may be 1 hour, the first time length may be 2 hours, or the first time length may be 3 hours.

[0050] In some embodiments, the coating amount of the electrolyte layer or electrolyte membrane layer is 0.2 g / cm 2 ~0.5g / cm 2 The length of the electrolyte layer or electrolyte membrane layer is 10 cm to 12 cm.

[0051] Specifically, the coating amount of the electrolyte membrane layer can be 0.2 g / cm 2 The electrolyte membrane coating amount can be 0.3g / cm 2 The coating amount of the electrolyte membrane layer can be 0.5g / cm 2 , the length of the electrolyte membrane layer can be 10 cm, the length of the electrolyte membrane layer can be 11 cm, and the length of the electrolyte membrane layer can be 12 cm.

[0052] Based on the same inventive concept, see Figure 3, the present application embodiment provides a battery preparation method, the method may include the following steps:

[0053] S302, uniformly coating the electrode slurry on the mold rod to form an anode film layer on the mold rod, and performing a first-stage sintering treatment on the anode film layer to obtain a hydrogen electrode;

[0054] S304, uniformly covering the hydrogen electrode with the electrolyte slurry to form an electrolyte layer on the hydrogen electrode, placing the hydrogen electrode coated with the electrolyte layer in an air environment, and sintering the hydrogen electrode at a second preset temperature for a second time to obtain an electrolyte membrane layer;

[0055] S306, uniformly coating the electrode slurry on the electrolyte membrane layer, forming a cathode membrane layer on the electrolyte membrane layer, and performing a third-stage sintering treatment on the cathode membrane layer to obtain an oxygen electrode;

[0056] S308, cutting and sealing the two ends of the oxygen electrode to obtain a battery.

[0057] In this embodiment, the hydrogen electrode coated with the electrolyte layer is placed in an air environment and sintered at a second preset temperature for a second time period, wherein the second preset temperature is 1250° C. to 1450° C. and the second time period is 3 hours to 5 hours.

[0058] Specifically, the electrode slurry is evenly coated on the electrode rod to form an anode film layer on the electrode rod, and the anode film layer is subjected to a first-stage sintering treatment to obtain an anode ceramic film layer, namely, an anode electrode layer, namely, a hydrogen electrode;

[0059] Further, the electrolyte slurry is uniformly coated on the anode film electrode to form an electrolyte layer on the anode film electrode, the anode film electrode coated with the electrolyte film layer is placed in an air environment, and sintered at a second preset temperature for a second time to obtain an electrolyte ceramic film layer, i.e., an electrolyte film layer;

[0060] Further, the electrode slurry is evenly coated on the electrolyte membrane electrode to form a cathode membrane on the electrolyte membrane electrode, and the cathode membrane is subjected to a third-stage sintering treatment to obtain a cathode ceramic membrane, i.e., an oxygen electrode;

[0061] Furthermore, the two ends of the SOEC blank composed of the anode ceramic membrane layer, the electrolyte ceramic membrane layer and the cathode ceramic membrane layer are cut neatly to obtain a single cell that meets the sealing test.

[0062] In some embodiments, the second preset temperature is 1250° C. to 1450° C., and the second time period is 3 hours to 5 hours.

[0063] Specifically, the second preset temperature may be 1250°C, the second preset temperature may be 1350°C, the second preset temperature may be 1450°C, the second time length may be 3 hours, the second time length may be 4 hours, and the second time length may be 5 hours.

[0064] In some embodiments, the cathode film coating amount is 0.5 g / cm 2 ~1g / cm 2 The length of the cathode film layer is 8cm to 10cm, and the length can be adjusted according to requirements.

[0065] Specifically, the cathode film coating amount can be 0.5 g / cm 2 , the cathode film coating amount can be 0.8g / cm 2 , the cathode film coating amount can be 1g / cm 2 , the cathode film layer length can be 8 cm, the cathode film layer length can be 9 cm, and the cathode film layer length can be 10 cm.

[0066] Based on the same inventive concept, see Figure 4 , the present application embodiment provides a battery preparation method, the method may include the following steps:

[0067] S402, uniformly coating the electrode slurry on the mold rod to form an anode film layer on the mold rod, and performing a first-stage sintering treatment on the anode film layer to obtain a hydrogen electrode;

[0068] S404, uniformly covering the hydrogen electrode with electrolyte slurry to form an electrolyte layer on the hydrogen electrode, and performing a second-stage sintering treatment on the electrolyte layer to obtain an electrolyte membrane layer;

[0069] S406, uniformly coating the electrode slurry on the electrolyte membrane layer, forming a cathode membrane layer on the electrolyte membrane layer, placing the electrode coated with the cathode membrane layer in an air environment, and sintering the electrode at a third preset temperature for a third time to obtain an oxygen electrode;

[0070] S408, cutting and sealing the two ends of the oxygen electrode to obtain a battery.

[0071] In this embodiment, the electrode coated with the cathode film layer is placed in an air environment and sintered at a third preset temperature for a third time, wherein the third preset temperature is 700° C. to 900° C. and the third time is 3 hours to 5 hours.

[0072] Specifically, the electrode slurry is evenly coated on the electrode rod to form an anode film layer on the electrode rod, and the anode film layer is subjected to a first-stage sintering treatment to obtain an anode ceramic film layer, namely, a hydrogen electrode;

[0073] Further, the electrolyte slurry is uniformly coated on the anode film electrode to form an electrolyte layer on the anode film electrode, and the electrolyte layer is subjected to a second-stage sintering treatment to obtain an electrolyte ceramic film layer, i.e., an electrolyte film layer;

[0074] Further, the electrode slurry is evenly coated on the electrolyte membrane electrode to form a cathode film layer on the electrolyte membrane electrode, the electrolyte membrane electrode coated with the cathode film layer is placed in an air environment, and sintered at a third preset temperature for a third time to obtain a cathode ceramic film layer, i.e., an oxygen electrode;

[0075] Furthermore, both ends of the rough SOEC single cell composed of the anode ceramic membrane layer, the electrolyte ceramic membrane layer and the cathode ceramic membrane layer are cut to obtain a single cell that can be sealed and tested.

[0076] In some embodiments, the third preset temperature is 700° C. to 900° C., and the third time period is 3 hours to 5 hours.

[0077] Specifically, the third preset temperature may be 700° C., the third preset temperature may be 800° C., the third preset temperature may be 900° C., the third time length may be 3 hours, the third time length may be 4 hours, and the third time length may be 5 hours.

[0078] Based on the same inventive concept, see Figure 5 , the present application embodiment provides a battery preparation method, the method may include the following steps:

[0079] S502, uniformly coating the electrode slurry on the mold rod to form an anode film layer on the mold rod, and performing a first-stage sintering treatment on the anode film layer to obtain a hydrogen electrode;

[0080] S504, uniformly covering the hydrogen electrode with electrolyte slurry to form an electrolyte layer on the hydrogen electrode, and performing a second-stage sintering treatment on the electrolyte layer to obtain an electrolyte membrane layer;

[0081] S506, uniformly coating the electrode slurry on the electrolyte membrane layer, forming a cathode membrane layer on the electrolyte membrane layer, and performing a third-stage sintering treatment on the cathode membrane layer to obtain an oxygen electrode;

[0082] S508, symmetrically cutting the two ends of the oxygen electrode attached with the anode film layer, the electrolyte film layer and the cathode film layer to obtain a battery of a preset length, and performing a sealing test on the battery.

[0083] In this embodiment, the electrode slurry is evenly coated on the electrode rod to form an anode film layer on the electrode rod, and the anode film layer is subjected to a first-stage sintering treatment to obtain an anode ceramic film layer, i.e., a hydrogen electrode;

[0084] Further, the electrolyte slurry is uniformly coated on the anode film electrode to form an electrolyte layer on the anode film electrode, and the electrolyte layer is subjected to a second-stage sintering treatment to obtain an electrolyte ceramic film layer, i.e., an electrolyte film layer;

[0085] Further, the electrode slurry is evenly coated on the electrolyte membrane electrode to form a cathode membrane on the electrolyte membrane electrode, and the cathode membrane is subjected to a third-stage sintering treatment to obtain a cathode ceramic membrane, i.e., an oxygen electrode;

[0086] Furthermore, the two ends of the blank SOEC single cell composed of the anode ceramic film layer, the electrolyte ceramic film layer and the cathode ceramic film layer are cut to obtain a single cell that can be sealed and tested. That is, the two ends of the blank SOEC battery are cut symmetrically to obtain a battery with neat ends and a preset length, which is convenient for the test stage and the obtained battery is subjected to a sealing test.

[0087] In some embodiments, the predetermined length of the battery of predetermined length is 9.5 cm to 10 cm.

[0088] Specifically, the preset length of the battery may be 9.5 cm, the preset length of the battery may be 9.8 cm, and the preset length of the battery may be 10 cm.

[0089] In some embodiments, the mold rod is a graphite rod.

[0090] Specifically, the graphite rod mold with a surface microporous structure can be replaced by other materials, such as a carbon rod, a wood rod, and other organic material rods, etc. That is, the mold rod can be a carbon rod, a wood rod, an organic material rod, etc.

[0091] In some embodiments, the length of the graphite rod is 17 cm to 19 cm, and the diameter of the graphite rod is 1 cm to 3 cm.

[0092] Specifically, the length of the graphite rod may be 17 cm, the length of the graphite rod may be 18 cm, and the length of the graphite rod may be 19 cm.

[0093] In some embodiments, the purity of the graphite rod is 99.9% to 99.99%.

[0094] Specifically, the purity of the graphite rod may be 99.9%, the purity of the graphite rod may be 99.95%, and the purity of the graphite rod may be 99.99%.

[0095] In some embodiments, see Figure 6 , before the step of uniformly coating the electrode slurry on the electrode rod, the method further comprises:

[0096] S602, grinding the electrode material and the electrode auxiliary material to obtain a first mixed slurry, and heating the first mixed slurry to obtain an electrode slurry;

[0097] S604, uniformly coating the electrode slurry on the mold rod to form an anode film layer on the mold rod, and performing a first-stage sintering treatment on the anode film layer to obtain a hydrogen electrode;

[0098] S606, uniformly covering the hydrogen electrode with electrolyte slurry to form an electrolyte layer on the hydrogen electrode, and performing a second-stage sintering treatment on the electrolyte layer to obtain an electrolyte membrane layer;

[0099] S608, uniformly coating the electrode slurry on the electrolyte membrane layer, forming a cathode membrane layer on the electrolyte membrane layer, and performing a third-stage sintering treatment on the cathode membrane layer to obtain an oxygen electrode;

[0100] S610, cutting and sealing the two ends of the oxygen electrode to obtain a battery.

[0101] In this embodiment, the electrode material is NiO-SDC, wherein the molar ratio of NiO to SDC in the electrode material is 7:3 or 6:4, and the electrode material is NiO-YSZ, wherein the molar ratio of NiO to YSZ in the electrode material is 7:3 or 6:4. The electrode auxiliary materials are pine alcohol, ethyl cellulose and a pore former, wherein the weight of the electrode material and the electrode auxiliary materials is: 1 to 3 parts by mass of NiO-SDC or NiO-YSZ, 2.5 to 4.5 parts by mass of pine alcohol, 0.1 to 0.2 parts by mass of ethyl cellulose, and 2 to 10 parts by mass of a pore former.

[0102] Taking 3g NiO-SDC as an example, the molar ratio of NiO to SDC is 7:3, wherein NiO is 1.49g and SDC is 1.51g.

[0103] Taking 3g NiO-SDC as an example, the molar ratio of NiO to SDC is 6:4, of which NiO is 1.17g and SDC is 1.83g.

[0104] Specifically, NiO-SDC or NiO-YSZ electrode slurry, wherein NiO accounts for 70% of the molar content of the electrode slurry, and the remaining 30% is the electrolyte SDC or YSZ. Electrode slurry configuration: 3.5g pineneol, 0.184g ethyl cellulose, pore-forming graphite, polyethylene glycol and other pore-forming agents, selected according to the pore size, an appropriate amount of ethanol as the pore-forming agent, and 2g NiO-SDC or NiO-YSZ are mixed and placed in a ball mill, which can be an agate jar, and ball milled at a speed of 300r / min for 12 hours, and heated at 65°C in a beaker for 4 to 6 hours to form a uniform viscous slurry.

[0105] In some embodiments, see Figure 7 , the electrode material and the electrode auxiliary material are mixed and ground, specifically including:

[0106] S702, mixing the electrode material and the electrode auxiliary material into a mixing and grinding device, mixing and grinding at a first speed for a fourth time to obtain a first mixed slurry, and heating the first mixed slurry to obtain an electrode slurry;

[0107] S704, uniformly coating the electrode slurry on the mold rod to form an anode film layer on the mold rod, and performing a first-stage sintering treatment on the anode film layer to obtain a hydrogen electrode;

[0108] S706, uniformly covering the hydrogen electrode with electrolyte slurry to form an electrolyte layer on the hydrogen electrode, and performing a second-stage sintering treatment on the electrolyte layer to obtain an electrolyte membrane layer;

[0109] S708, uniformly coating the electrode slurry on the electrolyte membrane layer, forming a cathode membrane layer on the electrolyte membrane layer, and performing a third-stage sintering treatment on the cathode membrane layer to obtain an oxygen electrode;

[0110] S710, cutting and sealing the two ends of the oxygen electrode to obtain a battery. In this embodiment, the electrode material and the electrode auxiliary material are mixed and placed in a mixing and grinding device, and mixed and ground at a first speed for a fourth time. The first speed is 250r / min to 350r / min, and the fourth time is 11 hours to 13 hours.

[0111] In some embodiments, the first rotation speed is 250 r / min to 350 r / min, and the fourth time length is 11 hours to 13 hours.

[0112] Specifically, the first speed may be 250 r / min, the first speed may be 300 r / min, the first speed may be 350 r / min, the fourth time length may be 11 hours, the fourth time length may be 12 hours, and the fourth time length may be 13 hours.

[0113] In some embodiments, see Figure 8 , heating the first mixed slurry, specifically comprising:

[0114] S802, grinding the electrode material and the electrode auxiliary material to obtain a first mixed slurry, placing the first mixed slurry in a container, and heating it at a fourth preset temperature for a fifth time to obtain an electrode slurry;

[0115] S804, uniformly coating the electrode slurry on the mold rod to form an anode film layer on the mold rod, and performing a first-stage sintering treatment on the anode film layer to obtain a hydrogen electrode;

[0116] S806, uniformly covering the hydrogen electrode with electrolyte slurry to form an electrolyte layer on the hydrogen electrode, and performing a second-stage sintering treatment on the electrolyte layer to obtain an electrolyte membrane layer;

[0117] S808, uniformly coating the electrode slurry on the electrolyte membrane layer, forming a cathode membrane layer on the electrolyte membrane layer, and performing a third-stage sintering treatment on the cathode membrane layer to obtain an oxygen electrode;

[0118] S810, cutting and sealing the two ends of the oxygen electrode to obtain a battery.

[0119] In this embodiment, the first mixed slurry is placed in a container and heated at a fourth preset temperature for a fifth time period, wherein the fourth preset temperature is 55° C. to 75° C., and the fifth time period is 4 hours to 6 hours.

[0120] In some embodiments, the fourth preset temperature is 55° C. to 75° C., and the fifth time period is 4 hours to 6 hours.

[0121] Specifically, the fourth preset temperature may be 55° C., the fourth preset temperature may be 65° C., the fourth preset temperature may be 75° C., the fifth time length may be 4 hours, the fifth time length may be 5 hours, and the fifth time length may be 6 hours.

[0122] In some embodiments, see Fig. 9 , before the step of uniformly covering the hydrogen electrode with the electrolyte slurry, the method further comprises:

[0123] S902, uniformly coating the electrode slurry on the mold rod to form an anode film layer on the mold rod, and performing a first-stage sintering treatment on the anode film layer to obtain a hydrogen electrode;

[0124] S904, grinding the electrolyte and the electrolyte auxiliary material to obtain a second mixed slurry, and heating the second mixed slurry to obtain an electrolyte slurry;

[0125] S906, uniformly covering the hydrogen electrode with electrolyte slurry to form an electrolyte layer on the hydrogen electrode, and performing a second-stage sintering treatment on the electrolyte layer to obtain an electrolyte membrane layer;

[0126] S908, uniformly coating the electrode slurry on the electrolyte membrane layer, forming a cathode membrane layer on the electrolyte membrane layer, and performing a third-stage sintering treatment on the cathode membrane layer to obtain an oxygen electrode;

[0127] S910, cutting and sealing the two ends of the oxygen electrode to obtain a battery.

[0128] In this embodiment, the electrolyte and the electrolyte auxiliary material are mixed and ground to obtain a second mixed slurry, and the second mixed slurry is heated to obtain an electrolyte slurry. The electrolyte is a solid YSZ electrolyte. The electrolyte auxiliary materials are pine alcohol and ethyl cellulose, wherein the electrolyte and the electrolyte auxiliary material are weighted as follows: 2 to 4 parts by weight of electrolyte, 2.5 to 4.5 parts by weight of pine alcohol, and 0.1 to 0.2 parts by weight of ethyl cellulose.

[0129] Specifically, the electrolyte slurry (YSZ) contains 3 g of electrolyte without pore-forming agent, and the electrolyte auxiliary materials are pine alcohol and ethyl cellulose, wherein the weights of the electrolyte and the electrolyte auxiliary materials are: 2 g to 4 g of electrolyte, 2.5 g to 4.5 g of pine alcohol, and 0.1 g to 0.2 g of ethyl cellulose.

[0130] In some embodiments, see Fig.10 , the electrolyte and electrolyte auxiliary materials are mixed and ground, specifically including:

[0131] S1002, uniformly coating the electrode slurry on the mold rod to form an anode film layer on the mold rod, and performing a first-stage sintering treatment on the anode film layer to obtain a hydrogen electrode;

[0132] S1004, mixing the electrolyte and the electrolyte auxiliary material into a mixing and grinding device, mixing and grinding at a second speed for a sixth time to obtain a second mixed slurry, and heating the second mixed slurry to obtain an electrolyte slurry;

[0133] S1006, uniformly covering the hydrogen electrode with electrolyte slurry to form an electrolyte layer on the hydrogen electrode, and performing a second-stage sintering treatment on the electrolyte layer to obtain an electrolyte membrane layer;

[0134] S1008, uniformly coating the electrode slurry on the electrolyte membrane layer, forming a cathode membrane layer on the electrolyte membrane layer, and performing a third-stage sintering treatment on the cathode membrane layer to obtain an oxygen electrode;

[0135] S1010, cutting and sealing the two ends of the oxygen electrode to obtain a battery.

[0136] In this embodiment, the electrolyte and the electrolyte auxiliary material are mixed and placed in a mixing and grinding device, and mixed and ground at the second speed for a sixth time, wherein the second speed is 250 r / min to 350 r / min, and the sixth time is 11 hours to 13 hours.

[0137] In some embodiments, the second rotation speed is 250 r / min to 350 r / min, and the sixth time length is 11 hours to 13 hours.

[0138] Specifically, the second speed may be 250 r / min, the second speed may be 300 r / min, the second speed may be 350 r / min, the sixth time length may be 11 hours, the sixth time length may be 12 hours, and the sixth time length may be 13 hours.

[0139] In some embodiments, see Fig.11 , heating the second mixed slurry, specifically comprising:

[0140] S1102, uniformly coating the electrode slurry on the mold rod to form an anode film layer on the mold rod, and performing a first-stage sintering treatment on the anode film layer to obtain a hydrogen electrode;

[0141] S1104, grinding the electrolyte and the electrolyte auxiliary material to obtain a second mixed slurry, placing the second mixed slurry in a container, and heating it at a fifth preset temperature for a seventh time to obtain an electrolyte slurry;

[0142] S1106, uniformly covering the hydrogen electrode with electrolyte slurry to form an electrolyte layer on the hydrogen electrode, and performing a second-stage sintering treatment on the electrolyte layer to obtain an electrolyte membrane layer;

[0143] S1108, uniformly coating the electrode slurry on the electrolyte membrane layer, forming a cathode membrane layer on the electrolyte membrane layer, and performing a third-stage sintering treatment on the cathode membrane layer to obtain an oxygen electrode;

[0144] S1110, cutting and sealing the two ends of the oxygen electrode to obtain a battery.

[0145] In this embodiment, the second mixed slurry is placed in a container and heated at a fifth preset temperature for a seventh time period, wherein the fifth preset temperature is 55° C. to 75° C., and the seventh time period is 4 hours to 6 hours.

[0146] In some embodiments, the fifth preset temperature is 55° C. to 75° C., and the seventh time period is 4 hours to 6 hours.

[0147] Specifically, the fifth preset temperature may be 55° C., the fifth preset temperature may be 65° C., the fifth preset temperature may be 75° C., the seventh time period may be 4 hours, the seventh time period may be 5 hours, and the seventh time period may be 6 hours.

[0148] In addition, the battery preparation method of the present application is suitable for a variety of electrolytes and electrode materials, including oxygen ion conductor electrolyte yttria stabilized zirconia (YSZ, SDC), perovskite electrolyte material LSGM, proton conductor electrolyte material BZSYYb, etc. This application takes YSZ material as electrolyte and NiO material as electrode as an example to demonstrate the preparation process of tubular single battery.

[0149] The use of NiO-YSZ or NiO-SDC mixed material for the cathode in this process is only an example, and the main purpose of this application is to protect the preparation technology of tubular single cells.

[0150] In some embodiments, Fig.12 As shown, the preparation process of the battery is as follows:

[0151] 1. Get a graphite rod mold;

[0152] 2. Anode tape casting: Specifically, the electrode slurry NiO-SDC or NiO-YSZ is coated on the electrode rod to form a uniform electrode film layer, i.e., the anode film layer. The amount of electrode film is 0.5 g / cm 2 ~1g / cm 2 Specifically, the amount of electrode slurry can be adjusted according to the required thickness, and pore-forming graphite, pore-forming fiber, etc. can be added according to the pore-forming requirements to coat the electrode.

[0153] 3. Sintering under nitrogen protection to protect the graphite rod; specifically, in a nitrogen atmosphere, the temperature is controlled to be 700° C. for sintering for 2 hours to form a 10 cm long supporting porous electrode, that is, an anode ceramic film layer, that is, a hydrogen electrode.

[0154] 4. Electrolyte casting: Specifically, the electrolyte slurry is coated on the electrode rod to form a uniform electrolyte layer. The electrolyte layer dosage is 0.2g / cm 2 ~0.5g / cm 2 , the specific thickness can be adjusted according to the required thickness.

[0155] 5. Sintering in air atmosphere; specifically, in air atmosphere, the temperature is controlled to be 1350° C. and sintered for 4 hours to form a dense electrolyte membrane layer that completely covers the supporting electrode layer. The length of the electrolyte membrane layer is 11 cm.

[0156] 6. Cathode tape casting: Specifically, the electrode slurry is evenly coated on the electrolyte film electrode to form a cathode film on the electrolyte ceramic film. The amount of electrode film is 0.5 g / cm 2 ~1g / cm 2 Specifically, the amount of electrode slurry can be adjusted according to the required thickness, and pore-forming graphite, pore-forming fiber, etc. can be added according to the pore-forming requirements to coat the electrode.

[0157] 7. Sintering in air atmosphere; specifically, in air atmosphere, the temperature is controlled to be 800° C. and sintered for 4 hours to form a 9 cm long oxygen evolution electrode, i.e., an oxygen electrode.

[0158] 8. Battery preparation is completed.

[0159] Based on the same inventive concept, an embodiment of the present application further provides a battery, which is prepared using the battery preparation method in any of the above embodiments.

[0160] Although this specification includes many specific implementation details, these should not be interpreted as limiting the scope of any invention or the scope of protection claimed, but are mainly used to describe the features of the specific embodiments of specific inventions. Certain features described in multiple embodiments in this specification may also be implemented in combination in a single embodiment. On the other hand, the various features described in a single embodiment may also be implemented separately in multiple embodiments or in any suitable sub-combination. In addition, although features may work in certain combinations as described above and even initially claim protection, one or more features from the claimed combination may be removed from the combination in some cases, and the claimed combination may point to a sub-combination or a variation of a sub-combination.

[0161] Similarly, although operations are depicted in a particular order in the accompanying drawings, this should not be understood as requiring that these operations be performed in the particular order shown or performed sequentially, or requiring that all illustrated operations be performed to achieve the desired results. In some cases, multitasking and parallel processing may be advantageous. In addition, the separation of various system modules and components in the above-described embodiments should not be understood as requiring such separation in all embodiments, and it should be understood that the described program components and systems can generally be integrated together in a single software product, or packaged into multiple software products.

[0162] Thus, specific embodiments of the subject matter have been described. Other embodiments are within the scope of the appended claims. In some cases, the actions recited in the claims can be performed in a different order and still achieve the desired results. In addition, the processes depicted in the drawings do not necessarily require the particular order or sequential order shown to achieve the desired results. In some implementations, multitasking and parallel processing may be advantageous.

[0163] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0164] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing a battery, characterized in that: The battery preparation method comprises: The electrode slurry is evenly coated on the mold rod to form an anode film layer on the mold rod, and the anode film layer is subjected to a first-stage sintering treatment to obtain a hydrogen electrode; Uniformly covering the hydrogen electrode with electrolyte slurry to form an electrolyte layer on the hydrogen electrode, and performing a second-stage sintering treatment on the electrolyte layer to obtain an electrolyte membrane layer; The electrode slurry is uniformly coated on the electrolyte membrane layer, a cathode membrane layer is formed on the electrolyte membrane layer, and the cathode membrane layer is subjected to a third-stage sintering treatment to obtain an oxygen electrode, wherein the anode membrane layer, the electrolyte layer and the cathode membrane layer are stacked and the anode membrane layer and the cathode membrane layer are separated by the electrolyte layer; Both ends of the oxygen electrode are cut and sealed to obtain a battery.

2. The battery preparation method according to claim 1, characterized in that: The coating amount of the anode film layer is 0.5 g / cm 2 ~1g / cm 2 , the length of the anode film layer is 9cm to 11cm.

3. The battery preparation method according to claim 1, characterized in that: The first stage sintering treatment of the anode film layer specifically includes: The mold rod coated with the anode film layer is placed in a nitrogen environment and sintered at a first preset temperature for a first time period.

4. The battery preparation method according to claim 3, characterized in that: The first preset temperature is 600° C. to 800° C., and the first time duration is 1 hour to 3 hours.

5. The battery preparation method according to claim 1, characterized in that: The electrolyte layer coating amount is 0.2 g / cm 2 ~0.5g / cm 2 , the length of the electrolyte layer is 10cm to 12cm.

6. The battery preparation method according to claim 1, characterized in that: The second stage sintering treatment of the electrolyte layer specifically includes: The hydrogen electrode coated with the electrolyte layer is placed in an air environment and sintered at a second preset temperature for a second period of time.

7. The battery preparation method according to claim 6, characterized in that: The second preset temperature is 1250° C. to 1450° C., and the second time period is 3 hours to 5 hours.

8. The battery preparation method according to claim 1, characterized in that: The cathode film coating amount is 0.5 g / cm 2 ~1g / cm 2 , the cathode film layer has a length of 8 cm to 10 cm.

9. The battery preparation method according to claim 1, characterized in that: The third stage sintering treatment of the cathode film layer specifically includes: The electrode coated with the cathode film layer is placed in an air environment and sintered at a third preset temperature for a third time period.

10. The battery preparation method according to claim 9, characterized in that: The third preset temperature is 700° C. to 1000° C., and the third time period is 3 hours to 5 hours.

11. The battery preparation method according to claim 1, characterized in that: The two ends of the oxygen electrode are cut and sealed to obtain a battery, specifically comprising: The two ends of the oxygen electrode attached with the anode film layer, the electrolyte film layer and the cathode film layer are symmetrically cut to obtain a battery of a preset length, and the battery is subjected to a sealing test.

12. The battery preparation method according to claim 11, characterized in that: The preset length is 9.5 cm to 10 cm.

13. The method for preparing a battery according to any one of claims 1 to 12, characterized in that: The mold rod is a graphite rod.

14. The method for preparing a battery according to claim 13, characterized in that: The length of the graphite rod is 17 cm to 19 cm, and the diameter of the graphite rod is 1 cm to 3 cm.

15. The method for preparing a battery according to claim 13, characterized in that: The purity of the graphite rod is 99.9% to 99.99%.

16. The battery preparation method according to claim 1, characterized in that: Before the step of uniformly coating the electrode slurry on the mold rod, the method further comprises: The electrode material and the electrode auxiliary material are mixed and ground to obtain a first mixed slurry, and the first mixed slurry is heated to obtain an electrode slurry.

17. The battery preparation method according to claim 16, characterized in that: The electrode material is NiO-SDC, wherein the molar ratio of NiO to SDC in the electrode material is 7:3 or 6:4; or The electrode material is NiO-YSZ, wherein the molar ratio of NiO to YSZ in the electrode material is 7:3 or 6:

4.

18. The battery preparation method according to claim 16, characterized in that: The electrode auxiliary materials are pine alcohol, ethyl cellulose and a pore former, wherein the electrode material and the electrode auxiliary materials have a weight ratio of: 1 to 3 parts by weight of NiO-SDC or NiO-YSZ, 2.5 to 4.5 parts by weight of pine alcohol, 0.1 to 0.2 parts by weight of ethyl cellulose and 2 to 10 parts by weight of a pore former.

19. The method for preparing a battery according to claim 16, characterized in that: The electrode material and the electrode auxiliary material are mixed and ground, specifically including: The electrode material and the electrode auxiliary material are mixed and placed in a mixing and grinding device, and mixed and ground at a first rotation speed for a fourth time.

20. The battery preparation method according to claim 19, characterized in that: The first rotation speed is 250 r / min to 350 r / min, and the fourth time length is 11 hours to 13 hours.

21. The method for preparing a battery according to claim 16, characterized in that: The heating treatment of the first mixed slurry specifically includes: The first mixed slurry is placed in a container and heated at a fourth preset temperature for a fifth time period.

22. The method for preparing a battery according to claim 21, characterized in that: The fourth preset temperature is 55° C. to 75° C., and the fifth time duration is 4 hours to 6 hours.

23. The battery preparation method according to claim 1, characterized in that: Before the step of uniformly covering the hydrogen electrode with the electrolyte slurry, the method further comprises: The electrolyte and the electrolyte auxiliary material are mixed and ground to obtain a second mixed slurry, and the second mixed slurry is heated to obtain an electrolyte slurry.

24. The method for preparing a battery according to claim 23, characterized in that: The electrolyte is a solid YSZ electrolyte.

25. The method for preparing a battery according to claim 23, characterized in that: The electrolyte auxiliary materials are pine alcohol and ethyl cellulose, wherein the weight of the electrolyte and the electrolyte auxiliary materials is: 2 g to 4 parts by weight of electrolyte, 2.5 to 4.5 parts by weight of pine alcohol, and 0.1 to 0.2 parts by weight of ethyl cellulose.

26. The method for preparing a battery according to claim 23, characterized in that: The mixing and grinding of the electrolyte and the electrolyte auxiliary material specifically comprises: The electrolyte and the electrolyte auxiliary material are mixed and placed in a mixing and grinding device, and mixed and ground at a second rotation speed for a sixth time.

27. The method for preparing a battery according to claim 26, characterized in that: The second rotation speed is 250 r / min to 350 r / min, and the sixth time length is 11 hours to 13 hours.

28. The method for preparing a battery according to claim 23, characterized in that: The heating treatment of the second mixed slurry specifically includes: The second mixed slurry is placed in a container and heated at a fifth preset temperature for a seventh time period.

29. The method for preparing a battery according to claim 28, characterized in that: The fifth preset temperature is 55° C. to 75° C., and the seventh time duration is 4 hours to 6 hours.

30. A battery, characterized in that: The battery is prepared by the battery preparation method according to any one of claims 1 to 29.